PERWATAKAN TOKOH BAIK (PROTAGONIS) DALAM PERTUNJUKAN WAYANG GOLEK MENAK - Sunarto Sunarto (Institut Seni Indonesia Surakarta, 2011)
Personalities and figure of protagonist in a menak puppet show is discussed in this study. Personalities and figure are described by using literary approach. In this study is limited to the characterization and disposition protagonists or characters that are good. Based on the results obtained by this approach are common changes and developments, both in characterization and disposition due to the inheritance orally. In this case, the mastermind horizon expectations have adjusted to personal views, educational background, and social and cultural life, the development of characterization and physical character creation visualize growing. The addition of new characters to the physical form and disposition are also new, emerging according to the reception puppeteerÂ and puppet maker puppet show artists.Key words : characterization, figure, protagonist, puppet